Renal C4d is a potential biomarker of disease activity and severity in pediatric lupus nephritis patients - Wang, Xueyao; Fu, Shaojie; Yu, Jinyu; Tang, Daru; Wu, Hao; Xu, Zhonggao (Frontiers in Pediatrics, 2023)
Background: Systemic lupus erythematosus (SLE), a multisystemic autoimmune disease, is very aggressive in pediatric-onset patients as they are prone to develop lupus nephritis (LN). Although renal C4d positivity is correlated with the activity of renal disease and SLE in adult-onset LN patients, available information for pediatric-onset patients is limited. Methods: To evaluate the potential diagnostic significance of renal C4d staining in pediatric LN patients, we retrospectively detected C4d staining by immunohistochemistry on renal biopsy specimens from 58 pediatric LN patients. The clinical and laboratory data at the time of the kidney biopsy and the renal disease activity of histological injury were analyzed according to the C4d staining status. Results: Glomerular C4d (G-C4d)-positive staining was detected in all 58 cases of LN. Patients with a G-C4d score of 2 displayed more severe proteinuria than those with a G-C4d score of 1 (24-h urinary protein: 3.40±3.55g vs. 1.36±1.24g, P<0.05). Peritubular capillary C4d (PTC-C4d) positivity was found in 34 of 58 LN patients (58.62%). The PTC-C4d-positive patient groups (patients with a PTC-C4d score of 1 or 2) had higher serum creatinine and blood urea nitrogen levels as well as renal pathological activity index (AI) and SLE disease activity index (SLEDAI) scores; however, they had lower serum complement C3 and C4 levels compared to PTC-C4d-negative patients (P<0.05). In addition, there was positive tubular basement membrane C4d (TBM-C4d) staining in 11 of 58 LN patients (18.96%), and a higher proportion of TBM-C4d-positive patients than TBM-C4d-negative patients (63.63% vs. 21.27%) had hypertension. Conclusion: Our study revealed that G-C4d, PTC-C4d, and TMB-C4d were positively correlated with proteinuria, disease activity and severity, and hypertension, respectively, in pediatric LN patients. These data suggest that renal C4d is a potential biomarker for disease activity and severity in pediatric LN patients, providing insights into the development of novel identification and therapeutic approaches for pediatric-onset SLE with LN.